2016
DOI: 10.1186/s12936-016-1542-9
|View full text |Cite
|
Sign up to set email alerts
|

Lay knowledge and management of malaria in Baringo county, Kenya

Abstract: BackgroundMalaria, a disease caused by protozoan parasites of the genus Plasmodium and transmitted by female anopheline mosquitoes, is a major cause of morbidity, mortality and loss in productivity in humans. Baringo County is prone to seasonal transmissions of malaria mostly in the rainy seasons.MethodsThis cross-sectional study used a mixed methods approach to collect data on knowledge and lay management of malaria. A questionnaire survey was administered to 560 respondents while qualitative data was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Fever, shivering/chills, headache, joint pain, and vomiting were stated as the cardinal signs of malaria. Fever was the predominantly (84%) recognized symptom of malaria in this study, consistent with studies from India [19], Uganda [23], and Kenya [24]. This may be due to the existence of high malaria infections since long time in the area.…”
Section: Discussionsupporting
confidence: 91%
“…Fever, shivering/chills, headache, joint pain, and vomiting were stated as the cardinal signs of malaria. Fever was the predominantly (84%) recognized symptom of malaria in this study, consistent with studies from India [19], Uganda [23], and Kenya [24]. This may be due to the existence of high malaria infections since long time in the area.…”
Section: Discussionsupporting
confidence: 91%
“…Misconceptions about malaria etiology were not unique to this study since similar perceptions have been reported among communities in western Kenya [ 28 ]. These misguided perceptions indicate a knowledge gap that potentially influence choices of malaria prevention or treatment pattern [ 29 ]. Thus, there is need for enhanced community knowledge though public education and awareness in order to increase uptake of preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the paucity in knowledge of RVF signs and symptoms may lead to misdiagnosis implicating other febrile ailments, such as malaria, that may be endemic in a region [ 34 ]. Inhabitants of Baringo County have been found to be knowledgeable of malaria signs the symptoms hence their ability to relate its symptomatology with that of RVF [ 35 ]. Unlike the Somalis in North Eastern Kenya who had a local name, “ sandik” (bloody nose), for RVF, [ 26 ], neither the Tugen nor Ilchamus had a widely accepted term possibly because the disease was reported for the first time in 2006–2007 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%